Social cognition in patients with schizophrenia spectrum and bipolar disorders with and without psychotic features() - Nitzburg, George C. (Schizophr Res Cogn, 2015)
BACKGROUND: Social cognition may be critical to the impoverished social functioning seen in serious mental illness. However, although social-cognitive deficits are consistently demonstrated in schizophrenia spectrum disorders (SSD), studies in bipolar disorder (BD) have produced inconsistent results. This inconsistency may relate to symptom profiles of patients studied, particularly the presence or absence of psychotic features. Thus, we examined social cognition in bipolar disorder with psychotic features (BD +) versus without psychotic features (BD −) relative to SSD and controls. METHODS: A sample of 537 SSD patients, 85 BD + patients, 37 BD − patients, and 309 controls were administered the MATRICS Consensus Cognitive Battery, including a social cognition measure, the managing emotions branch of the Mayer–Salovey–Caruso Emotional Intelligence Test (MSCEIT). Analyses of covariance compared MSCEIT performance between diagnostic groups while controlling for race, psychotropic medication status, and neurocognition. RESULTS: SSD but not BD − or BD + patients showed significant MSCEIT deficits relative to controls. CONCLUSIONS: MSCEIT deficits were found in SSD but not BD − or BD +, suggesting that social cognition may represent an underlying difference between SSD and BD. However, variance in MSCEIT performance among BD patients may also suggest latent BD subgroups characterized by social-cognitive deficits. Findings can help inform future investigations into how social cognition and social brain development differ between SSD and BD.